Unveiling the Psychological Consequences of Illness Perception in Pediatric Multiple Sclerosis: A Parent-Child Study - Roy Aloni; Gaya Asher; Amichai Ben-Ari; Shay Menascu (MDPI AG, 2024)
Background: Previous research has emphasized the significant role of illness perception in chronic diseases, including Multiple Sclerosis. Limited research has been conducted on exploring illness perception in Pediatric Onset Multiple Sclerosis (POMS), parental illness perception, and the impact of differences in their illness perceptions on the emotional well-being of the child. Method: This study included 65 dyads of children aged 10-17 and their parents, divided into the following two groups: (I) 32 dyads of children with POMS and their parents; and (II) 33 dyads of healthy children and their parents. Results: Overall, 73.1% and 43.8% of the children with POMS met the criteria for probable anxiety and depression, respectively, compared to 27.3% and 0% of the healthy children. Differences were found between the dimensions of illness perception in the POMS children and their parents, in the areas of consequences, personal control, identity, and control factors. Multinomial Logistic Regression indicated that differences in child-parent illness perception increased the likelihood of comorbid anxiety and depression by 37%. Discussion: These findings underscore the importance of alignment between children with POMS and their parents in illness perception. Healthcare providers should prioritize interventions that address illness perceptions and be mindful of the potential impact on depression and anxiety comorbidity.